Financial Statement Analysis: Using Financial Accounting Information (Book). - Meyer, Philip E.; Williamson, Robert W. (The Accounting Review, 1984)
Abstract Reviews the book "Financial Statement Analysis: Using Financial Accounting Information," 2nd ed., by Charles H. Gibson and Patricia A. Frishkoff.